Synergistic Inactivation of Bacteria Using a Combination of Erythorbyl Laurate and UV Type-A Light Treatment - Chang, Yoonjee; Bai, Jaewoo; Yu, Hyunjong; Chang, Pahn-Shick; Nitin, Nitin (Frontiers in Microbiology, 2021)
This study evaluated the synergistic antimicrobial activity of erythorbyl laurate (EL) and ultraviolet type-A (UVA). To investigate the mode of synergism, changes in gene expression and bacterial inactivation activity were examined. Individual treatments with EL (10 mM) or UVA caused a 1.9- or 0.5-log CFU/mL reduction respectively, whereas EL/UVA co-treatment resulted in a 5.5-log CFU/mL reduction in Escherichia coli viable cell numbers. Similarly, treatment with either EL (2 mM) or UVA for 30 min resulted in a 2.8- or 0.1-log CFU/mL reduction in Listeria innocua, respectively, whereas combined treatment with both EL and UVA resulted in a 5.4-log CFU/mL reduction. Measurements of gene expression levels showed that EL and UVA treatment synergistically altered the gene expression of genes related to bacterial membrane synthesis/stress response. However, addition of 10 to 50-fold excess concentration of exogenous antioxidant compared to EL reduced the synergistic effect of EL and UVA by approximately 1 log. In summary, the results illustrate that synergistic combination of EL and UVA enhanced membrane damage independent of the oxidative stress damage induced by UVA and thus illustrate a novel photo-activated synergistic antimicrobial approach for the inactivation of both the Gram-positive and Gram-negative bacteria. Overall, this study illustrates mechanistic evaluation of a novel photochemical approach for food and environmental applications.